PRODUKTIVITAS TANAMAN KALIANDRA (Calliandra calothyrsus) SEBAGAI HIJAUAN PAKAN PADA UMUR PEMOTONGAN YANG BERBEDA - Abqoriyah (Abqoriyah); Ristanto Utomo; Bambang Suwignyo (Buletin Peternakan, 2015)
This research aimed to determine the production and nutrient content of calliandra (Caliandra calothyrsus) as a forage for ruminant in the different defoliation time. This research was conducted for 48 weeks (June 2012–June 2013) at Kaligesing forage feed area, Animal Science Department, Purworejo, Central Java. Design of the research was Completely Randomized Block Design. Soil slope was used as block. The research treatments were 6 (P1), 8 (P2), 12 (P3) and 16 (P4) weeks of cutting age. The grass of all treatment groups were cut together at the same day prior to experiment. Caliandra calothyrsus was cut at edible portion. Parameters measured were fresh forage, dry matter, organic matter and crude protein production and also nutrient content namely dry matter, organic matter, crude protein, extract ether, crude fiber, BETN and TDN. The result showed that the highest dry matter content was found in P3 (31.25%) and was different from P1 (26.51%) and P4 (28.12%). The highest crude protein content was found in P2 (21.10%) and was not different with P1 (21.09%) and P3 (19.20%), and the lowest crude protein was found inP4 (18.04%). The highest extract ether was at P3 (2.84%) and different from P1 (1.51%). The highest crude fiber was at P4 (22.56%) different with P1 (15.80%) and P2 (18.46%). Organic matter, BETN and TDN were not different among the different defoliation time. The highest fresh forage, dry matter, organic matter and crude protein production were at P4 and different (P<0.05) from P1, P2 and P3. The lowest dry matter was at P2. It is concluded that the best quality of grass was found in P3 group and the highest harvesting quantity was found in P4 group.(Key words: Calliandra calothyrsus, Cutting age, Nutrient content, Production)